Regulation of cough by secondary sensory inputs - Hanáček, Ján; Tatár, Miloš; Widdicombe, John G (Respiratory physiology & neurobiology, 2006)
We have reviewed the role of afferent inputs and blood chemical changes to the central nervous system, and the way in which they modify the cough and expiration reflexes (CR and ER). Slowly adapting pulmonary stretch receptors (SARs) augment the CR, insofar as when their activity is abolished the CRs from the tracheobronchial (TB) tree and larynx are abolished or weakened. However, stimulation of SARs by lung inflation has an inconsistent effect on the CR. Activation of SARs strongly potentiates the ER from the vocal folds, by a reflex mechanism, and inhibition of SARs weakens the ER. Bronchopulmonary C-fibre receptors inhibit the CR, as do capsaicin-sensitive afferents from the heart and splanchnic bed, cutaneous cold receptors and those that respond to chest wall vibration. Nasal receptors responsive to the irritant agent capsaicin potentiate the reflex. Acute hypoxia also augments the CR, and the reflex is down-regulated by carotid body resection. On the other hand, the CR is inhibited by prolonged hypoxia and hyperoxia, and by hypercapnia. Thus different inputs to the cough-controlling mechanism in the brainstem have very varied effects on the CR. We conclude that the sensitivities of the CR and ER can be modified in a large variety of physiological and clinical conditions, and that there is no clear relationship between the reflexes and changes in breathing caused by the interventions.
Keywords: Pulmonary Stretch Receptors; plicní tahové receptory; Respiratory System; dýchací soustava; Afferent Pathways; Respiratory Physiological Phenomena; kašel; Animals; Humans; fyziologie dýchací soustavy; lidé; aferentní nervové dráhy; zvířata; Heart; Cough; srdce